Campostriniite, (Bi3+, Na)3(NH4, K)2Na2(SO4)6·H2O, a new sulfate isostructural with görgeyite, from La Fossa Crater, Vulcano, Aeolian Islands, Italy. (2nd January 2018) - Demartin, Francesco; Castellano, Carlo; Gramaccioli, Carlo Maria
Abstract: The new mineral campostriniite, (Bi 3+, Na)3 (NH4, K)2 Na2 (SO4 )6 ·H2 O, was found in an active fumarole (fumarole FA, temperature ∼350°C) at La Fossa Crater, Vulcano, Aeolian Islands, Sicily, Italy. It occurs on a pyroclastic breccia as white prismatic crystals up to 0.2 mm long, in association with adranosite, demicheleite-(Br), demicheleite-(I), argesite and sassolite. The mineral is monoclinic, space group: C 2/ c (no. 15) with a = 17.748(3), b = 6.982(1) c = 18.221(3) Å, β = 113.97(1)°, V = 2063(1) Å 3 and Z = 4. The six strongest reflections in the powder X-ray diffraction pattern are: [dobs in Å ( I )( hkl )] 6.396(100)(110), 7.507(75)(202), 2.766(60)(316), 3.380(57)(312), 5.677(55)(111), 3.166(50)(4 0 2). The empirical formula (based on 25 anions p.f.u.) is Bi2.41 N1.52 Na2.41 K0.48 S6.07 H8.08 O25 . The calculated density is 3.87 g cm –3 . Using single-crystal diffraction data, the structure was refined to a final R ( F ) = 0.051 for 3025 independent observed reflections [ I > 2σ( I )]. Campostriniite is isostructural with görgeyite and belongs to the 7.CD group of the Strunz classification system. The structure contains two independent nine-fold coordinated sites, one of them located on a two-fold axis (M1) and the other one in general position (M2) essentially occupied by Bi 3+ atoms and minor amounts of Na + ions, an eight-fold coordinated site fully occupied by Na +ions and another eight-fold coordinated site occupied by NH + 4 and K + ions; three independent sulfate anions in a general position and a water molecule coordinated to M1 and located on a two-fold axis are also present.